Polyarylene sulfide composition
A blend of amino group-modified polyarylene sulfide, ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid butyl ester copolymer, and fillers enhances both dimensional accuracy and heat cycle resistance, addressing the limitations of existing compositions.
Patent Information
- Application Number
- JP2021019863
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-10
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-02-10
AI Technical Summary
Existing polyarylene sulfide resin compositions face challenges in achieving both high dimensional accuracy and heat cycle resistance, particularly in harsh conditions.
A specific blend of amino group-modified polyarylene sulfide, ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid butyl ester copolymer, fibrous filler, and powdery filler, in specific proportions, to enhance weld rupture energy and improve both dimensional accuracy and heat cycle resistance.
The composition achieves high dimensional accuracy and excellent heat cycle resistance, suitable for electrical and electronic components, with a weld breaking energy of 0.34 J or more, making it suitable for insert-molded composite members.
Smart Images

Figure 0007608853000001 
Figure 0007608853000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyarylene sulfide composition having excellent heat cycle resistance and dimensional accuracy, and in particular to a polyarylene sulfide composition highly loaded with a filler that exhibits a specific weld rupture energy and thus has heat cycle resistance and dimensional accuracy that are particularly useful for electrical component applications such as electric / electronic components or automotive electrical components. [Background technology]
[0002] Polyarylene sulfide is a resin that exhibits excellent properties such as heat resistance, chemical resistance, and dimensional stability, and is widely used in electrical and electronic equipment components, automotive equipment components, and office equipment components, taking advantage of these excellent properties. In recent years, higher dimensional accuracy is required for automotive equipment components as automobiles become more highly functional. Furthermore, as automobiles are increasingly used under more severe heat cycle conditions, they are also required to have excellent heat cycle resistance (toughness).
[0003] In attempts to improve the dimensional accuracy of polyarylene sulfide, for example, a resin composition consisting of (a) polyphenylene sulfide resin, (b) polyphenylene ether resin, (c) glass fiber, and (d) calcium carbonate (see, for example, Patent Document 1), and a resin composition consisting of (a) polyphenylene sulfide resin, (b) polyphenylene ether resin, (c) glass fiber, and (d) kaolin (see, for example, Patent Document 2), etc. have been proposed, all of which are characterized by being highly filled with filler.
[0004] Attempts to improve the toughness of polyarylene sulfide have been proposed, for example, a resin composition consisting of (a) polyarylene sulfide and (e) an ethylene-α,β-unsaturated carboxylic acid alkyl ester copolymer (see, for example, Patent Document 3); a resin composition consisting of a composition obtained by melt-kneading (a) polyphenylene sulfide and a non-blocked polyfunctional isocyanate compound and (e) an ethylene-α,β-unsaturated carboxylic acid alkyl ester copolymer (see, for example, Patent Document 4); a resin composition consisting of (a) polyarylene sulfide, (e) an ethylene-α,β-unsaturated carboxylic acid alkyl ester copolymer, and (f) a specific type of alkoxysilane compound (see, for example, Patent Document 5); and a resin composition consisting of (a) polyarylene sulfide, (e) a polyolefin resin, and (f) a polymer containing an alkoxysilane group (see, for example, Patent Document 6). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2008-007758 A [Patent Document 2] Japanese Patent Application Publication No. 09-157525 [Patent Document 3] Japanese Patent Application Laid-Open No. 62-151460 [Patent Document 4] Japanese Patent Application Publication No. 02-255862 [Patent Document 5] Japanese Patent Application Publication No. 05-202245 [Patent Document 6] Japanese Patent Application Publication No. 04-164962 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the resin compositions proposed in Patent Documents 1 and 2 have problems with heat cycle resistance and toughness, and the resin compositions proposed in Patent Documents 3 to 6 have problems with dimensional accuracy, and therefore have problems in achieving both high dimensional accuracy and heat cycle resistance.
[0007] SUMMARY OF THE PRESENT EMBODIMENTS Accordingly, an object of the present invention is to provide a polyarylene sulfide composition which is highly loaded with a filler and which has both high dimensional accuracy and heat cycle resistance. [Means for solving the problem]
[0008] As a result of intensive research aimed at solving the above problems, the inventors have discovered that a polyarylene sulfide composition that can achieve both high dimensional accuracy and heat cycle resistance can be obtained by blending at least a specific polyarylene sulfide, a specific carboxylate butyl ester group-containing polyethylene, a fibrous filler, and a powdery filler in specific amounts and by achieving a specific weld rupture energy, thereby completing the present invention.
[0009] That is, the present invention relates to a polyarylene sulfide composition comprising 35 to 50% by weight of an amino group-modified polyarylene sulfide (A) having 0.05 to 3 mol % of amino groups per arylene sulfide unit and having a melt viscosity of 200 to 1000 poise measured under conditions of a measurement temperature of 315°C and a load of 10 kg using a high-temperature flow tester equipped with a die having a diameter of 1 mm and a length of 2 mm, 2 to 9% by weight of an ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid butyl ester copolymer (B), 35 to 60% by weight of a fibrous filler (C), and 1 to 20% by weight of a powdery filler (D), wherein the total proportion of the fibrous filler (C) and the powdery filler (D) is 45% by weight or more, and the weld rupture energy evaluated using a dumbbell test piece in accordance with ASTM D638 test piece (Type-1) is 0.34 J or more.
[0010] The present invention will be described in detail below.
[0011] The amino group-modified polyarylene sulfide (A) constituting the polyarylene sulfide composition of the present invention can be generally referred to as polyarylene sulfide, and can include those that contain units having amino groups at the terminal units or in-chain units of polyarylene sulfide.Then, the units of polyarylene sulfide constituting the amino group-modified polyarylene sulfide can be, for example, p-phenylene sulfide units, m-phenylene sulfide units, o-phenylene sulfide units, phenylene sulfide sulfone units, phenylene sulfide ketone units, phenylene sulfide ether units, biphenylene sulfide units, etc., and polyarylene sulfide is a homopolymer or copolymer of these units. Specific examples of the amino group-modified polyarylene sulfide include amino group-modified polyphenylene sulfide, amino group-modified polyphenylene sulfide sulfone, amino group-modified polyphenylene sulfide ketone, amino group-modified polyphenylene sulfide ether, etc., and among these, amino group-modified poly(p-phenylene sulfide) is preferred because it results in a polyarylene sulfide composition that is particularly excellent in heat resistance and strength properties.
[0012] The amino group-modified polyarylene sulfide (A) constituting the present invention has 0.05 to 3 mol % of amino groups per arylene sulfide unit, and preferably 0.1 to 2 mol % since it results in a polyarylene sulfide composition with particularly excellent heat cycle resistance. The amino group-modified polyarylene sulfide (A) can be produced by adding an amino group-containing dihalogen aromatic compound at 0.05 to 3 mol %, preferably 0.1 to 2 mol %, based on the total amount of the polyhalogenated aromatic compound and the amino group-containing dihalogen aromatic compound during the preparation example of the amino group-modified polyarylene sulfide described later.
[0013] The amino group-modified polyarylene sulfide (A) constituting the present invention is a high-quality polyarylene sulfide composition with few impurities, and therefore, when producing the amino group-modified polyarylene sulfide, it is preferable to carry out high-pressure hot water treatment and washing after polymerization. The high-pressure hot water treatment conditions at this time include washing in a water system with a temperature of 150°C to 240°C.
[0014] The method for producing the amino group-modified polyarylene sulfide (A) is not particularly limited, and it may be produced by a method generally known as a method for producing polyarylene sulfides using an amino group-containing polyhalogenated aromatic compound. For example, it can be produced by a method of reacting an alkali metal sulfide with a polyhalogenated aromatic compound and an amino group-containing polyhalogenated aromatic compound in a polymerization solvent.
[0015] In this case, the polymerization solvent is preferably a polar solvent, and particularly preferably an organic amide solvent that is aprotic and stable against high-temperature alkali. As the organic amide solvent, any solvent that falls within the category of organic amide solvents can be used, such as N,N-dimethylacetamide, N,N-dimethylformamide, hexamethylphosphoramide, N-methyl-ε-caprolactam, N-ethyl-2-pyrrolidone, N-methyl-2-pyrrolidone, 1,3-dimethylimidazolidinone, dimethylsulfoxide, sulfolane, tetramethylurea, and mixtures thereof. As the polyhalogenated aromatic compound, any compound that belongs to the category of polyhalogenated aromatic compounds can be used. Examples of the polyhalogenated aromatic compound include p-dichlorobenzene, m-dichlorobenzene, o-dichlorobenzene, p-dibromobenzene, m-dibromobenzene, o-dibromobenzene, p,p'-dichlorodiphenyl, p,p'-dibromodiphenyl, 2,6-dichloronaphthalene, 2,6-dibromonaphthalene, 1,3,5-trichlorobenzene, and 1,2,4-trichlorobenzene. Among these, p-dichlorobenzene is preferred because it is easier to obtain polyarylene sulfide having a high molecular weight and excellent mechanical properties. Examples of the amino group-containing polyhalogenated aromatic compound include 2,5-dichloroaniline, 2,6-dibromonaphthalene, and the like. Examples of the alkali metal sulfide include chloroaniline, 3,5-dichloroaniline, 3,5-diaminochlorobenzene, 2-amino-4-chlorotoluene, 2-amino-6-chlorotoluene, 4-amino-2-chlorotoluene, 3-chloro-m-phenylenediamine, 2,5-dibromoaniline, 2,6-dibromoaniline, 3,5-dibromoaniline, and mixtures thereof. In particular, 3,5-dichloroaniline and 3,5-diaminochlorobenzene are preferred. As the alkali metal sulfide, any one that belongs to the category of alkali metal sulfides can be used. Examples of the alkali metal sulfide include sodium sulfide anhydrous, sodium sulfide 2.8 hydrate, sodium sulfide pentahydrate, and other sodium sulfides, lithium sulfide, rubidium sulfide, sodium hydrogen sulfide, and lithium hydrogen sulfide.
[0016] The amino group-modified polyarylene sulfide (A) constituting the present invention is preferably heat-treated under an inert gas atmosphere at a temperature of 150° C. to 260° C., particularly preferably at a temperature of 170° C. to 250° C. Examples of the inert gas include nitrogen and argon.
[0017] The amino group-modified polyarylene sulfide (A) constituting the present invention has a melt viscosity of 200 to 1000 poise, measured using a high-temperature flow tester equipped with a die having a diameter of 1 mm and a length of 2 mm under conditions of a measurement temperature of 315°C and a load of 10 kg. If the melt viscosity is less than 200 poise, the resulting composition will have poor heat cycle resistance. On the other hand, if the melt viscosity is more than 1000 poise, the resulting composition will have poor melt fluidity and poor moldability.
[0018] The amount of the amino group-modified polyarylene sulfide (A) constituting the polyarylene sulfide composition of the present invention is 35 to 50% by weight. If the amount of the amino group-modified polyarylene sulfide (A) is less than 35% by weight, the resulting composition will have poor molding flowability. On the other hand, if it exceeds 50% by weight, the resulting composition will have poor dimensional accuracy.
[0019] As the ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid butyl ester copolymer (B) constituting the polyarylene sulfide composition of the present invention, any one may be used as long as it belongs to this category, and among them, since the obtained polyarylene sulfide composition is excellent in toughness, it is preferable that it is composed of ethylene residue unit:α,β-unsaturated carboxylic acid glycidyl ester residue unit:α,β-unsaturated carboxylic acid butyl ester residue unit (weight ratio) in the range of = 60 to 93: 2 to 10: 5 to 30. Specific examples of the ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid butyl ester copolymer include, for example, (trade name) LOTADER AX8700 (manufactured by Arkema Co., Ltd.), (trade name) LOTADER AX8750 (manufactured by Arkema Co., Ltd.), etc. The present invention has discovered that by combining an amino group-modified polyarylene sulfide with the ethylene-α,β-unsaturated carboxylic acid glycidyl-α,β-unsaturated carboxylic acid butyl ester copolymer, a composition can be obtained that exhibits superior heat cycle resistance to previously proposed compositions, such as polyarylene sulfide and ethylene-α,β-unsaturated carboxylic acid glycidyl ester copolymer, ethylene-α,β-unsaturated carboxylic acid glycidyl ester-vinyl ester copolymer, ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid methyl ester copolymer, ethylene-α,β-unsaturated carboxylic ester-maleic anhydride copolymer, ethylene-α-olefin-maleic anhydride copolymer, etc.
[0020] The polyarylene sulfide composition of the present invention contains 2 to 9% by weight of ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid butyl ester copolymer (B), and if the amount of ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid butyl ester copolymer (B) is less than 2% by weight, the resulting composition has poor heat cycle resistance, and if it exceeds 9% by weight, the resulting composition has poor molding flowability.
[0021] Examples of the fibrous filler (C) constituting the polyarylene sulfide composition of the present invention include glass fibers such as chopped strands, milled fibers, and rovings having an average fiber diameter of 8 to 15 μm; carbon fibers such as PAN-based carbon fibers and pitch-based carbon fibers; whiskers such as graphitized fibers, silicon nitride whiskers, basic magnesium sulfate whiskers, barium titanate whiskers, potassium titanate whiskers, silicon carbide whiskers, boron whiskers, and zinc oxide whiskers; metal fibers such as stainless steel fibers; inorganic fibers such as rock wool, zirconia, alumina silica, barium titanate, silicon carbide, alumina, silica, and blast furnace slag; organic fibers such as wholly aromatic polyamide fibers, phenolic resin fibers, and wholly aromatic polyester fibers; and mineral fibers such as wollastonite and magnesium oxysulfate. In particular, glass fibers having an average fiber diameter of 8 to 15 μm and a round cross-sectional shape are preferred because they result in a polyarylene sulfide composition with excellent heat cycle resistance. Two or more of these may be used in combination, and if necessary, the surface may be previously treated with a functional compound or polymer such as an epoxy compound, an isocyanate compound, a silane compound, or a titanate compound.
[0022] The polyarylene sulfide composition of the present invention contains 35 to 60% by weight of fibrous filler (C), and if the amount of fibrous filler (C) is less than 35% by weight, the resulting composition is inferior in heat cycle resistance and dimensional accuracy, and if it exceeds 60% by weight, the resulting composition is inferior in heat cycle resistance and molding flowability.
[0023] Examples of the powdery filler (D) constituting the polyarylene sulfide composition of the present invention include powdery fillers such as calcium carbonate, lithium carbonate, magnesium carbonate, zinc carbonate, mica, silica, talc, clay, calcium sulfate, kaolin, wollastonite, zeolite, glass powder, alumina, silicon oxide, magnesium oxide, zirconium oxide, iron oxide, tin oxide, magnesium silicate, calcium silicate, calcium phosphate, magnesium phosphate, graphite, carbon black, glass powder, glass balloons, glass flakes, hydrotalcite, and metal foils. Among these, calcium carbonate having an average particle size of 1 to 7 μm is preferred because it provides a polyarylene sulfide composition that is excellent in balance of mechanical strength and excellent in heat cycle resistance. Two or more of these can also be used in combination, and if necessary, it may be surface-treated in advance with a functional compound or polymer such as an epoxy compound, an isocyanate compound, a silane compound, or a titanate compound.
[0024] The polyarylene sulfide composition of the present invention contains 1-20% by weight of the powdery filler (D), and if the amount of the powdery filler (D) exceeds 20% by weight, the resulting composition will have poor heat cycle resistance, and if it is less than 1% by weight, the dimensional accuracy, particularly the anisotropy, will be poor.
[0025] The polyarylene sulfide composition of the present invention contains the fibrous filler (C) and the particulate filler (D) in a total amount of 45% by weight or more. If the total amount of the fibrous filler (C) and the particulate filler (D) is less than 45% by weight, the resulting composition will have poor dimensional accuracy.
[0026] The polyarylene sulfide composition of the present invention has a weld rupture energy of 0.34 J or more, evaluated using a dumbbell test piece conforming to the ASTM D638 test piece (Type-1). If the composition has a weld rupture energy of less than 0.34 J, when it is made into a composite with a metal member, it will have poor heat cycle resistance and will be prone to problems such as cracking and destruction. The weld rupture energy can be calculated as the area enclosed by a stress-strain curve obtained by performing a weld strength test.
[0027] Furthermore, the polyarylene sulfide composition of the present invention may contain a silane coupling agent (E) consisting of a trialkoxysilane coupling agent having a glycidyl group and / or a trialkoxysilane coupling agent having an amino group, a dialkoxysilane coupling agent and / or a dialkoxysilane coupling agent having an amino group, since it has particularly excellent heat cycle resistance. In this case, the silane capping agent (E) is not particularly limited as long as it is a trialkoxysilane coupling agent having a glycidyl group or an amino group, and specific examples of those belonging to this category include 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, etc. The amount of the silane coupling agent (E) is preferably 0.01 to 0.5% by weight.
[0028] The polyarylene sulfide composition of the present invention may contain a release agent for improving the mold releasability and appearance when molded into a molded product, within the scope of the present invention. As the release agent, for example, polyethylene wax, polypropylene wax, and fatty acid amide wax are preferably used. As the polyethylene wax and polypropylene wax, general commercial products can be used. In addition, the fatty acid amide wax is a polycondensate of higher aliphatic monocarboxylic acid, polybasic acid, and diamine, and any wax that falls within this category can be used. For example, Light Amide WH-255 (trade name, manufactured by Kyoeisha Chemical Co., Ltd.), which is a polycondensate of stearic acid, sebacic acid, and ethylenediamine, can be mentioned.
[0029] Furthermore, the polyarylene sulfide composition of the present invention can be used by mixing one or more of various thermosetting resins and thermoplastic resins, such as epoxy resins, cyanate ester resins, phenolic resins, polyimides, silicone resins, polyesters, polyamides, polyphenylene oxides, polycarbonates, polysulfones, polyetherimides, polyethersulfones, polyetherketones, and polyetheretherketones, within the scope of the object of the present invention.
[0030] Furthermore, the polyarylene sulfide composition of the present invention may contain one or more additives, such as conventionally known heat stabilizers, antioxidants, ultraviolet absorbers, crystal nucleating agents, foaming agents, mold corrosion inhibitors, flame retardants, flame retardant assistants, colorants such as dyes and pigments, and antistatic agents, within the scope of the object of the present invention.
[0031] The polyarylene sulfide composition of the present invention can be produced by a conventionally used heating melt kneading method. For example, a heating melt kneading method using a single-screw or twin-screw extruder, a kneader, a mill, a Brabender, etc. is mentioned, and a melt kneading method using a twin-screw extruder with excellent kneading ability is particularly preferred. The kneading temperature is not particularly limited, and can be selected from 280 to 400°C. The polyarylene sulfide composition of the present invention can be molded into any shape using an injection molding machine, an extrusion molding machine, a transfer molding machine, a compression molding machine, etc.
[0032] The polyarylene sulfide composition of the present invention is characterized by having both high dimensional accuracy and excellent heat cycle resistance. Furthermore, the polyarylene sulfide composition of the present invention can be used as an insert molding composite member by insert molding into other members, particularly metal members, etc.
[0033] The insert metal member used in the insert molding composite member may be made of any metal as long as it belongs to the category of metals, and among them, steel, copper, stainless steel, aluminum, magnesium, brass, and nickel are preferred, and steel and copper are particularly preferred, since the resulting insert molding composite member can be adapted to various uses. The insert metal member may be rolled or cast.
[0034] The shape of the insert metal member is not particularly limited as long as it is a shape that can be insert molded. Also, one or more insert metal members may be used.
[0035] In insert molding, an insert metal member is attached to a mold, and the polyarylene sulfide composition heated and melted at 290 to 340°C can be molded under normal molding conditions using an injection molding machine, an extrusion molding machine, a compression molding machine, etc., and injection insert molding using an injection molding machine is particularly preferred from the viewpoint of production efficiency.
[0036] The polyarylene sulfide composition of the present invention and the insert-molded composite member made therefrom have high dimensional accuracy and heat cycle resistance, and can be applied to electric and electronic parts such as sensors, connectors, relay cases, coil bobbins, capacitors, various terminal boards, small motors, motor brush holders, computer-related parts, and the like; and automotive parts such as valve alternator terminals, alternator connectors, IC regulators, exhaust gas sensors, cooling water sensors, oil temperature sensors, throttle position sensors, crankshaft position sensors, brake pad wear sensors, radiator motor brush holders, water pump impellers, water pump inlets, starter relays, wire harnesses, fuse connectors, horn terminals, electrical component insulating plates, step motor rotors, solenoid bobbins, ignition device cases, vehicle speed sensors, capacitor cases, ECU cases, power module cases, power control units, coil bobbins, motor terminal blocks, reactors, batteries, bus bars, inverters, and insulators. Effect of the Invention
[0037] The present invention relates to a polyarylene sulfide composition which realizes high dimensional accuracy by being highly filled with a filler and has excellent heat cycle resistance, and which is particularly useful for electrical part applications such as electric / electronic parts or automotive electrical parts. EXAMPLES
[0038] The present invention will now be described with reference to examples, but the present invention is not limited to these examples in any way.
[0039] Details of the polyarylene sulfide, fibrous filler, powdery filler, ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid butyl ester copolymer, and silane coupling agent used in the examples and comparative examples are shown below.
[0040] <Polyarylene sulfide (A)> Amino group-modified poly(p-phenylene sulfide) (A1-2) (hereinafter simply referred to as PPS (A1-2)): melt viscosity 480 poise. Amino group content 0.15% by weight. Poly(p-phenylene sulfide) (hereinafter simply referred to as PPS (A2-2)): melt viscosity 560 poise.
[0041] <Ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid butyl ester copolymer (B)> Ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid butyl ester copolymer (B-1) (hereinafter simply referred to as polyethylene copolymer (B-1)): manufactured by Arkema Co., Ltd., (product name) LOTADER AX8700, ethylene residue unit: methacrylic acid glycidyl ester residue unit: acrylic acid butyl ester residue unit (weight ratio) = 67:8:25. Ethylene-α,β-unsaturated carboxylic acid alkyl ester-maleic anhydride copolymer (B-2) (hereinafter simply referred to as ethylene copolymer (B-2)): manufactured by Arkema Co., Ltd., (product name) Bondine AX8390, ethylene residue unit: maleic anhydride residue unit: acrylic acid ester residue unit (weight ratio) = 68: 1.5: 30.5. Ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid vinyl ester copolymer (B-3) (hereinafter simply referred to as polyethylene copolymer (B-3)): manufactured by Sumitomo Chemical Co., Ltd., (product name) Bondfast 2B, ethylene residue unit: methacrylic acid glycidyl ester residue unit: vinyl acetate ester residue unit (weight ratio) = 83:12:5 <Fibrous filler (C)> Glass fiber (C-1); Nippon Electric Glass Co., Ltd., (product name) ECS03T-760H (fiber length 10.5 μm, round cross-sectional shape) <Powdered filler (D)> Calcium carbonate (D-1); manufactured by Shiraishi Kogyo Co., Ltd., (product name) Whiten P-30; average particle size 4 μm. Calcium carbonate (D-2); Shiraishi Kogyo Co., Ltd., (product name) Whiten P-10; average particle size 2 μm.
[0042] <Silane coupling agent (E)> Trialkoxysilane coupling agent having a glycidyl group (E-1); manufactured by Shin-Etsu Chemical Co., Ltd., (product name) KBM-403; 3-glycidoxypropyltrimethoxysilane. Trialkoxysilane coupling agent having an amino group (E-2): manufactured by Shin-Etsu Chemical Co., Ltd., (trade name) KBM-603; N-2-(aminoethyl)-3-aminopropyltrimethoxysilane.
[0043] Synthesis Example 1 In a 50-liter autoclave equipped with a stirrer, 6214 g of Na2S·2.9H2O and 17000 g of N-methyl-2-pyrrolidone were charged, and the mixture was gradually heated to 205°C while stirring under a nitrogen stream, and 1355 g of water was distilled off. After cooling the system to 140°C, 7120 g of p-dichlorobenzene, 12 g of 3,5-dichloroaniline (approximately 0.15 mol% relative to the total amount of p-dichlorobenzene and 3,5-dichloroaniline), and 5000 g of N-methyl-2-pyrrolidone were added, and the system was sealed under a nitrogen stream. The system was heated to 225°C over 2 hours, polymerized at 225°C for 2 hours, then heated to 250°C over 30 minutes, and polymerized at 250°C for another 3 hours. After the polymerization was completed, the mixture was cooled to room temperature, and the solids were isolated by centrifugation. The solid content was washed with hot water at 225° C. and dried at 100° C. for one day to obtain amino group-modified poly(p-phenylene sulfide) (hereinafter referred to as PPS (A1-1)).
[0044] This PPS (A1-1) was cured at 250°C for 4 hours in a nitrogen atmosphere to obtain amino group-modified poly(p-phenylene sulfide) (hereinafter referred to as PPS (A1-2)). The melt viscosity of PPS (A1-2) was 480 poise, and the amino group content was 0.15% by weight.
[0045] The evaluation and measurement methods for the obtained polyarylene sulfide are shown below.
[0046] ~Melt viscosity measurement~ The melt viscosity was measured using a high-temperature flow tester (manufactured by Shimadzu Corporation, product name CFT-500) equipped with a die having a diameter of 1 mm and a length of 2 mm, under conditions of a measurement temperature of 315° C. and a load of 10 kg.
[0047] ~Measurement of weld rupture energy~ Test pieces were prepared using an injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., product name: SE-75S), and measurements were performed using a tensile testing machine (manufactured by Shimadzu Corporation, product name: Autograph AG-5000B) in accordance with ASTM D638.
[0048] ~Heat cycle resistance~ A test piece for heat cycle resistance was prepared by insert molding using an injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., product name: SE-75S) to insert a rectangular parallelepiped steel material (carbon steel) of 30 mm x 20 mm x 10 mm, and covering it with a polyarylene sulfide composition having a thickness of 1 mm. The obtained test piece was subjected to a heat cycle in which one cycle was held at 150°C for 30 minutes and then at -40°C for 30 minutes, and the cycle was continued until cracks were visually observed to occur, and the number of heat cycle treatments at which cracks were observed to occur was evaluated as heat cycle resistance. A test piece with a heat cycle treatment number of 100 cycles or more was judged to have excellent heat cycle resistance.
[0049] ~Dimensional accuracy~ Dumbbell test pieces conforming to the test piece (Type-1) were prepared using an injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., product name: SE-75S), and the dimensions in the width direction were measured. Those with a shrinkage rate of 0.2% or less were deemed to have excellent dimensional accuracy.
[0050] Example 1 PPS (A1-2) 84.3 wt%, polyethylene copolymer (B-1) 9.4 wt%, calcium carbonate (D-1) 5.7 wt%, silane coupling agent (E-1) 0.6 wt% were mixed and fed into the hopper of a twin-screw extruder (Toshiba Machine, (product name) TEM-35-102B) heated to a cylinder temperature of 310 ° C. On the other hand, glass fiber (C-1) was fed into the hopper of the side feeder of the twin-screw extruder, melt-kneaded at a screw rotation speed of 180 rpm, and the molten composition flowing out of the die was cooled and then cut to prepare a pellet-shaped polyarylene sulfide composition. The composition ratio of the polyarylene sulfide composition at that time was 44.7 wt% PPS (A1-2), 5 wt% polyethylene copolymer (B-1), 47 wt% glass fiber (C-1), 3 wt% calcium carbonate (D-1), and 0.3 wt% silane coupling agent (E-1).
[0051] The polyarylene sulfide composition was put into the hopper of an injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., (product name) SE75) heated to a cylinder temperature of 310° C., and a test piece for measuring the weld rupture energy and a test piece for measuring the heat cycle resistance were molded and evaluated. The results are shown in Table 1.
[0052] The resulting polyarylene sulfide composition was excellent in dimensional accuracy, weld rupture energy, and heat cycle resistance.
[0053] Examples 2 to 7 A polyarylene sulfide composition was prepared in the same manner as in Example 1, except that the PPS (A1-2), polyethylene copolymer (B-1), glass fiber (C-1), calcium carbonate (D-1), and silane coupling agents (E-1, E-2) were mixed in the proportions shown in Table 1, and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0054] All of the obtained polyarylene sulfide compositions had high dimensional accuracy, a weld rupture energy of 0.34 J or more, and excellent heat cycle resistance.
[0055] [Table 1] Comparative Examples 1 to 8 Polyarylene sulfide compositions were prepared in the same manner as in Example 1, except that the PPS (A1-2, A2-2), polyethylene copolymers (B-1, B-2, B-3), glass fiber (C-1), calcium carbonate (D-1, D-2), and silane coupling agent (E-1) were mixed in the proportions shown in Table 2, and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.
[0056] The compositions obtained in the comparative examples were inferior in heat cycle resistance and / or dimensional accuracy.
[0057] [Table 2] [Industrial Applicability]
[0058] The polyarylene sulfide composition of the present invention relates to a polyarylene sulfide composition which realizes high dimensional accuracy by being highly filled with a filler and has excellent heat cycle resistance, and is particularly useful for electrical part applications such as electric / electronic parts or automotive electrical parts.
Claims
1. A mixture of 35 to 50% by weight of an amino group-modified polyarylene sulfide (A) having 0.05 to 3 mol % of amino groups per arylene sulfide unit and having a melt viscosity of 200 to 1,000 poise measured using a high-temperature flow tester equipped with a die having a diameter of 1 mm and a length of 2 mm under the conditions of a measurement temperature of 315° C. and a load of 10 kg, 2 to 9% by weight of an ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid butyl ester copolymer (B), 35 to 60% by weight of a fibrous filler (C), and A polyarylene sulfide composition comprising 1 to 20% by weight of a granular filler (D), the total ratio of the fibrous filler (C) and the granular filler (D) being 45% by weight or more, and further comprising 0.01 to 0.5% by weight of at least one silane coupling agent (E) selected from the group consisting of a trialkoxysilane coupling agent having a glycidyl group, a trialkoxysilane coupling agent having an amino group, a dialkoxysilane coupling agent having a glycidyl group, and a dialkoxysilane coupling agent having an amino group, the composition having a weld rupture energy of 0.34 J or more and a shrinkage rate in the width direction of 0.2% or less, as evaluated using a dumbbell test piece in accordance with the test piece (Type-1) of ASTM D638.
2. 2. The polyarylene sulfide composition according to claim 1, wherein the amino group-modified polyarylene sulfide (A) is a high-pressure hot water-washed amino group-modified polyarylene sulfide.
3. The polyarylene sulfide composition according to claim 1 or 2, characterized in that the fibrous filler (C) is a glass fiber having an average fiber diameter of 8 to 15 μm and a round cross-sectional shape, and the powdery granular filler (D) is calcium carbonate having an average particle diameter of 1 to 10 μm.
4. An insert-molded composite member, which is an insert molding of the polyarylene sulfide resin composition according to any one of claims 1 to 3 and a metal member.
Citation Information
Patent Citations
Polyarylene sulfide resin composition
JP1987151460A
Composition based on polyphenylene sulfide
JP1990255862A
Polyarylene sulfide resin composition and production thereof
JP1992164962A
Polyarylene sulfide resin composition
JP1993202245A
Polyphenylene sulfide resin composition for precision molding
JP1997157525A